Application of Geophysics for the Detection of Derangement of Phosphate Layers in the Oulad Abdoun Basin in Morocco - E., Zerouali; A., Wafik; A., Najine; F., Radouani; S., Didi; M., Alaoui (European Scientific Journal, ESJ, 2018)
The phosphate series of the basin of Oulad Abdoun begins in Maastrichtian with phosphate deposits relatively very marly. It ends at the Lutetian by a calcareous slab. Derangement is any disruption of the usual succession of the phosphate series and that which disrupts the evolution of the kinematic chain, leading to a decrease in production and profitability. In this case, we have a partially disturbed series and the disturbance consists of all the elements of the series (limestone, flint, marls and phosphate). The present work has been carried out in two ways: The present work has been carried out in two ways: The first one, purely geological, consists of the identification of the different layers of the Ouled Abdoun basin in the El Halassa site and their continuity to the outcrop. At the end of these observations, the basin shows derangement of two kinds: a disturbance on the scale of the whole series known as major disturbance, and a second which affects only part of the series. Thus, it is a minor or local disturbance. The second one, geophysics, is the application of three geophysical methods: electric tomography, magnetism, and refraction seismic. The correlation of these applications should result in delineating the mineralized zone and tracking all elements that in one way or another affect this mineralization. These elements are referred to as "derangement". The combination of the results of these two methods (vertical electrical survey and tomography) used allowed us to identify and map the disturbed places in the chosen area of El Halassa. The study will be extended to other sites and the results can be compared and correlated to understand the extent and origin of these disturbances.